Induced Early Flowering Mutants in Dendrocalamus strictus Nees: after Gamma Irradiation - Kapoor, M. L.; Sharma, V. K. (Indian Forester, 1992)
Induced mutants showing precocious flowering in Dendrocalamus strictus Nees. Through gamma irradiation of seeds have been reported. The mutants flowered at the age 15 months when they were still in pots, though normally this species takes 20 to 40 years to flower. Studies were done on their pollen grain size and fertility. The plant did not set seeds. The cause of premature flowering and its utilization in breeding programmes has been discussed.